2022
DOI: 10.1177/23259671221083568
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Versus Rigid Reaming Systems for Independent Femoral Tunnel Reaming During ACL Reconstruction: Minimum 2-Year Clinical Outcomes

Abstract: Background: Radiographic and cadaveric studies have suggested that anatomic anterior cruciate ligament reconstruction (ACLR) femoral tunnel drilling with the use of a flexible reaming system through an anteromedial portal (AM-FR) may result in a different graft and femoral tunnel position compared with using a rigid reamer through an accessory anteromedial portal with hyperflexion (AAM-RR). No prior studies have directly compared clinical outcomes between the use of these 2 techniques for femoral tunnel creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Moreover, it may necessitate complex, staged management for revision ACL surgery, including initial bone grafting procedures to fill the widened tunnels [ 10 , 22 , 23 ]. This complication is not only related to surgical techniques but also to the type of fixation devices, graft selection, and demographic factors [ 12 , 15 , 16 , 19 , 24 , 25 ]. The relation between tunnel widening and clinical outcomes remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it may necessitate complex, staged management for revision ACL surgery, including initial bone grafting procedures to fill the widened tunnels [ 10 , 22 , 23 ]. This complication is not only related to surgical techniques but also to the type of fixation devices, graft selection, and demographic factors [ 12 , 15 , 16 , 19 , 24 , 25 ]. The relation between tunnel widening and clinical outcomes remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have hypothesized that tunnel widening potentially serves as an early finding of graft failure. However, many recent studies could not find any relationship between tunnel enlargement and the clinical results after surgery, and only a few have demonstrated the impact on the clinical outcome of tunnel widening [ 15 , 16 , 21 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thomas E Moran et al concluded that no significant differences in strength assessments or patient-reported outcomes at 6 months postoperatively in Flexible Versus Rigid Reaming Systems for Independent Femoral Tunnel making research 18 , some researchers confirmed that the flexible reamer system can be considered a safe and effective method for reconstruction surgery 19 . For Flexible reamer in our research, no associated complications were found , in addition to its safeness, we found some other advantages: (1) All-inside arthroscopic operation become possible.…”
Section: Discussionmentioning
confidence: 99%